Modelo de pronóstico para la cantidad por paquete y las ventas en soles de gaseosas de la empresa Rubio SAC - Sisniegas Langle, Rosa Elena (2011)
The prognosis models are by their same definition tools to quantify phenomena to develop methodologies for the decision making. Taking into account this situation the following problem considered: What is the forecast model and the quantity per package in domestic sales of the company Rubio SAC?_x000D_ By means of the prognosis models we can put financial and commercial phenomena in statistical terms, which allow to see the things us from the suitable perspective and low terms directly applied to the case, finally to make a decision that allows so much the economic efficiency as technical in the companies. Specifically, Models ARIMA will be the objective of this investigation. One says that models ARIMA reflect the behavior of a phenomenon through a certain period._x000D_ Coming to determine the forecasting model estimated for the series of the quantity per package sold by the company Rubio SAC is the ARIMA (0,1,2), the estimated forecasting model for the historical series in domestic sales Rubio SAC by the company, is the ARIMA (0,1,1). And the forecast estimates for the series of the quantity per package sold by the company Rubio SAC, according to the ARIMA (0,1,2) for the next 3 weeks are: 1 ° 1524.34, 1513.24 and 2nd with 3º to 1513.24, the forecast estimates for the time series of sales of the company Rubio soles SAC, according to the ARIMA (0,1,1) for the next 3 weeks are: 1 ° with 19025.7, 19025.7 and 2 ° and 3º with 19025.7